ANALISIS PENGARUH KREDIT, BEBAN OPERASIONAL SERTA NON PERFORMING LOANS TERHADAP MODAL DI PT. BANK PANIN, TBK. - Reyner F. Makatita (Universitas Nusa Cendana, 2015)
Credit is a source of revenue and profits for banks. Credit also is an activity that cause theproblem to the banks. We know that the largest revenue in the bank that can affect the capital is theinterest come from lending. The increasing of the loan portfolio will increase the interest incomegained, increasing of the revenue will cover the entire load including the non-performing loan(NPL). After deducting income and the burden of non-performing loans (NPL), it will acquireprofit. Since the loan portfolio provides different income, each bank made different lending policiesin order to increase the amount of capital, although there are other income excluding interest, forexample: administrative costs of savings and transfer services. Keywords : Credit, Operating Expenses, Non-performing loan (NPL), Bank Capital.